2012
DOI: 10.1111/j.1750-3841.2012.02762.x
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp Waste Extract and Astaxanthin: Rat Alveolar Macrophage, Oxidative Stress and Inflammation

Abstract: The hydrolysis process of shrimp waste generates bioactive products that add economic value to shrimp processing, mainly because they may have applications in nutraceutical and animal feed industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 49 publications
0
36
0
3
Order By: Relevance
“…Krill oil is a marine-derived oil rich in phospholipids, astaxanthin, and omega-3 polyunsaturated fatty acids (Costanzo et al 2016). According to a previous study, astaxanthin is known to have an anti-inflammatory effect (Santos et al 2012). In addition, Ohata et al (1997) previously reported that suppression of NO production was observed with the omega-3 polyunsaturated fatty acids such as DHA and EPA in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Krill oil is a marine-derived oil rich in phospholipids, astaxanthin, and omega-3 polyunsaturated fatty acids (Costanzo et al 2016). According to a previous study, astaxanthin is known to have an anti-inflammatory effect (Santos et al 2012). In addition, Ohata et al (1997) previously reported that suppression of NO production was observed with the omega-3 polyunsaturated fatty acids such as DHA and EPA in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The commercial ethanol (92.8 °) was used since it enables a better extraction with less cost and it is a less toxic solvent (Santos et al, 2012).…”
Section: Shrimp Filletmentioning
confidence: 99%
“…The carotenoid pigments were extracted from the shrimp waste (15 g) through homogenization with 92.8 ° ethanol (100 mL) in a blender during 5 min (Santos et al, 2012). Each crude extract was then centrifuged (10,000 rpm/4 °C, 10 min), and the supernatant (liquid phase) stored in amber bottles.…”
Section: Shrimp Waste (Shells Tail and Paws)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, antioxidant status of the shrimp fed dietary treatments was not determined. However, previous studies have found that carotenoids decreased the levels of TBARs (thiobarbituric acid-reactive substances), indicating lipid peroxidation (da Silva et al, 2015;Palozza et al, 2008;Sallam et al, 2017), alleviating oxidative damage (Santos et al, 2012) and limiting free radical molecule production caused by cellular metabolism and other various stressors (Pan et al, 2010).…”
Section: Growth Survival and Biomass Production Of Shrimpmentioning
confidence: 99%